2020
DOI: 10.1016/j.psj.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Selection response and genetic parameter estimation of feeding behavior traits in Pekin ducks

Abstract: Body weight–related traits and feeding behavior traits are important in poultry breeding and production. To investigate the heritability of feeding behavior and their genetic correlation with body weight–related traits in Pekin ducks, 5,594 Pekin ducks were selected. The information about body weight–related traits and feeding behavior from 3 to 6 wk of age were recorded by automatic electronic feeders. The heritability estimates for body weight, residual feed intake, and feeding behavior traits are relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
5
12
0
Order By: Relevance
“…Moreover, NM had relatively strong negative genetic and phenotypic correlations (≤ − 0.63) with MFI and MD in this study. Similar intensely negative phenotypic and genetic relationships (ranging from − 0.49 to − 0.93) were obtained in our former work [ 11 ]. It suggested that certain feeding behavior habits may affect feed consumption in ducks.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, NM had relatively strong negative genetic and phenotypic correlations (≤ − 0.63) with MFI and MD in this study. Similar intensely negative phenotypic and genetic relationships (ranging from − 0.49 to − 0.93) were obtained in our former work [ 11 ]. It suggested that certain feeding behavior habits may affect feed consumption in ducks.…”
Section: Discussionsupporting
confidence: 87%
“…It suggested that certain feeding behavior habits may affect feed consumption in ducks. Previous researches also reported that feeding behavior traits were closely associated with RFI levels while having little impact on body weight in ducks [ 10 , 11 ]. Combined with these findings, selecting certain feeding behavior traits could be an effective way to achieve indirect selection for RFI without affecting body weight improvement in Pekin ducks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of significant differences may be associated with the fact that the flock of birds was homogeneous regardless of sex. It is related to significant advances in breeding, where restrictive selection affects many traits of ducks [ 40 ]. Zeolite may influence gut morphology (the size and shape of the intestinal villi), the intestinal microbiota, and the digestibility of proteins and increase the levels of the apparent metabolizable energy (AME; AME N ) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%